Persistence, retention, and interruption in higher education among Peruvian scholarship students in a context of emergency remote learning - (:unkn) unknown (Arizona State University, 2024)
In Latin America, higher education inequality disproportionately affects individuals from low socioeconomic backgrounds, and Peru is no exception. Since 2012, the National Scholarship and Student Loan Programme (PRONABEC) has disbursed grants, aiming to ...
Keywords: Educación superior; Aprendizaje remoto